Motivasi Mustahik dalam Pemberdayaan Ekonomi melalui Zakat Produktif di LAZIS Jateng Banjarnegara Pendekatan Teori Self-Determination - Rizka Cahya Kamila; Anggita Sukma Puri; M. Ahda Dzikri; Mahardhika Cipta Raharja (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study was conducted to determine what motivates mustahik in economic empowerment through the productive zakat program at the Banjarnegara branch of LAZIS Central Java. This study used the Self-Determination Theory (SDT) approach and qualitative methods with a case study type to gain a deeper understanding of the experiences, drives, and factors that influence mustahik's motivation in developing their businesses after receiving productive zakat assistance. Data were collected through interviews, observations, and documentation with mustahik beneficiaries and program managers. Data analysis used qualitative analysis techniques that included data collection, data presentation, and drawing conclusions. The results showed that mustahik's motivation in economic empowerment was influenced by both internal and external factors. Internal motivation was evident in their desire to improve their welfare and achieve economic independence. External motivation came from business capital assistance, mentoring from institutions, family support, and urgent economic needs. However, some mustahik still depended on external assistance so that their economic independence had not been fully achieved. Viewed from the perspective of Self-Determination Theory, this condition indicates that basic psychological needs such as autonomy, competence, and relatedness had not been met properly. Therefore, continuous mentoring, strengthening of business capacity, and empowerment strategies are needed that not only provide financial assistance, but also build motivation from within the mustahik so that they can achieve sustainable economic independence. Keywords: motivation mustahik, productive zakat, economic empowerment, Self-Determination Theory.